2022
DOI: 10.1039/d1ra07647g
|View full text |Cite
|
Sign up to set email alerts
|

Generation of multi-valence CuxO by reduction with activated semi-coke and their collaboration in the selective reduction of NO with NH3

Abstract: In this work, we systematically analyzed the structure–activity relationship and synergistic mechanism of activated semi-coke (ASC)-loaded multi-valence CuxO for the low-temperature NO-SCR process by NH3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…14 Additionally, Peng et al achieved satisfactory low-temperature SCR activity by loading Cu x O onto activated semicoke (ASC). 15 Bjorkedal et al also synthesized highly dispersed copper catalysts supported on mesoporous ZrO 2 carriers using a sol–gel approach and evaluated their performance in NH 3 -SCR. 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Additionally, Peng et al achieved satisfactory low-temperature SCR activity by loading Cu x O onto activated semicoke (ASC). 15 Bjorkedal et al also synthesized highly dispersed copper catalysts supported on mesoporous ZrO 2 carriers using a sol–gel approach and evaluated their performance in NH 3 -SCR. 16…”
Section: Introductionmentioning
confidence: 99%
“…14 Additionally, Peng et al achieved satisfactory low-temperature SCR activity by loading Cu x O onto activated semicoke (ASC). 15 Bjorkedal et al also synthesized highly dispersed copper catalysts supported on mesoporous ZrO 2 carriers using a sol-gel approach and evaluated their performance in NH 3 -SCR. 16 To broaden the operational temperature range and enhance the performance of catalysts, the incorporation of a third metallic element has proven to be an effective strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it was reported that copper oxides demonstrate excellent catalytic activity in LT SCR reactions. In order to prevent secondary pollution of equipment corrosion caused by NH 3 , C is used as an effective reductant, which also has excellent adsorption of NO x . Hence, the composites of copper oxides and C have been extensively investigated. For instance, the CuO-decorated C nanotubes and activated C-supported CuO only show high activity for NO conversion at temperatures ranging from 120 to 250 °C . Nonetheless, the catalytic activity decreases as the temperature exceeds 250 °C, indicating the structural instability of CuO/C composites at higher temperatures, which however remains largely unexplored.…”
mentioning
confidence: 99%